2015
DOI: 10.1002/jnr.23701
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related synaptic dysfunction in Tg2576 mice starts as a failure in early long‐term potentiation which develops into a full abolishment of late long‐term potentiation

Abstract: Tg2576 mice are widely used to study amyloid-dependent synaptic dysfunction related to Alzheimer's disease. However, conflicting data have been reported for these mice with regard to basal transmission as well as the in vitro correlate of memory, long-term potentiation (LTP). Some studies show clear impairments, whereas others report no deficiency. The present study uses hippocampal slices from 3-, 10-, and 15-month-old wild-type (WT) and Tg2576 mice to evaluate synaptic function in each group, including exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 120 publications
2
3
0
Order By: Relevance
“…2c-d; t- test: t (22) = 0.37, p = 0.72). These results are in agreement with previous observations showing normal CA3-CA1 LTP in young adult APP transgenics including APP/PS1 [26, 27], J20 [42], and Tg2576 mice [13, 19]. Thus, the behavioural and CA3-CA1 synaptic phenotype of developmental-onset line 102 APP Sw,Ind mice is highly similar to that previously observed in other young APP transgenic models that also express APP from embryonic and/or postnatal development.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2c-d; t- test: t (22) = 0.37, p = 0.72). These results are in agreement with previous observations showing normal CA3-CA1 LTP in young adult APP transgenics including APP/PS1 [26, 27], J20 [42], and Tg2576 mice [13, 19]. Thus, the behavioural and CA3-CA1 synaptic phenotype of developmental-onset line 102 APP Sw,Ind mice is highly similar to that previously observed in other young APP transgenic models that also express APP from embryonic and/or postnatal development.…”
Section: Resultssupporting
confidence: 92%
“…Developmental-onset mice showed a substantial disruption of basal synaptic transmission consistent with previous studies in several APP lines [16, 31, 33]. Nevertheless, similar to other young-adult developmental APP models, we found that despite high levels of Aβ, developmental onset APP/tTA mice exhibited normal levels of NMDAR-dependent hippocampal LTP in CA3-CA1 synapses (which was inhibited by APV, data not shown) [13, 19, 26, 27, 32, 42]. These results are in stark contrast to the impaired LTP we observed in mature-onset mice with a similar duration of APP expression, and even though there were lower Aβ levels in the mature-onset model.…”
Section: Discussionsupporting
confidence: 90%
“…Although this animal model is widely used to study amyloiddependent synaptic dysfunctions, reported findings vary regarding the extent to which basal neurotransmission and LTP are affected (33)(34)(35)(36)(37). Possible explanations for the high variability in this model include differences in the age of the Tg2576 animals and various experimental parameters (38). Our functional characterization of aged 9-mo-old Tg2576 mice revealed reduced basal neurotransmission and synaptic plasticity compared to age-matched WT mice; however, the decrease in LTP reached significant levels only at the early initial phase (0 to 10 min), which can be considered a shortterm plasticity effect.…”
Section: Discussionmentioning
confidence: 99%
“…Like the TCblR/ CD320 KO mouse, the Tg2576 mouse model shows normal basal synaptic transmission and PPF but deteriorated LTP [59]. The Tg2576 mouse model accumulates beta-amyloid and generates oxidative stress as well as mitochondrial dysfunction [60], and reduction of oxidative stress in this mouse model prevents learning and memory deficits [61].…”
Section: Discussionmentioning
confidence: 99%